2020
DOI: 10.1089/whr.2020.0043
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Genital Arousal Disorder After Motor Vehicle Accident: A Case Report

Abstract: Persistent genital arousal disorder (PGAD) is a clinical syndrome characterized by persistent unwanted feelings of sexual arousal that are not associated with any specific sexual arousal or stimulus. The severity of symptoms range from mild to severe distress that interrupts daily life for patients. We present a 44-year-old previously healthy woman who developed PGAD after involvement in a motor vehicle accident in 2018. After sustaining lower spinal trauma, 3 months later, she began to experience intermittent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In fact, it has been reported that the symptoms of PGAD/GPD due to trauma and other problems responded relatively well to physical treatments [ 5 , 6 ]. Our patient underwent various tests, but no organic cause was observed; however, she had received many physical treatments due to the severity of her symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that the symptoms of PGAD/GPD due to trauma and other problems responded relatively well to physical treatments [ 5 , 6 ]. Our patient underwent various tests, but no organic cause was observed; however, she had received many physical treatments due to the severity of her symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The associated unsettling elements include restless legs syndrome and signs of an overactive bladder. In a clinical study, Waldinger and Schweitzer reported that shaking legs occurred in 67% of 18 women with a final diagnosis of PGAD (Parus et al, 2020). Similar to postural instability disorder (PGAD), restless leg syndrome symptoms intensify in response to immobility and improve with lower limb movement or stimulation.…”
Section: Neurological and Psychiatric Factors In Pgadmentioning
confidence: 99%
“…Radiculopathy of sacral spinal nerve roots within the cauda equina or sacrum are contributors to PGAD/GPD. 23,24,125 Temporary iatrogenic radiculopathy producing PGAD/GPD symptoms has been noted after sacral neuromodulation. 126 In 2012, Komisaruk and Lee first reported the occurrence of sacral Tarlov cysts in women with PGAD symptoms, which were previously thought to be incidental radiologic findings.…”
Section: Region 3: Cauda Equinamentioning
confidence: 99%
“…These intervertebral disc pathologies can be mechanical (disc bulge or herniation impinging against the dura and the nerve roots) or chemical due to annular tear. 125 Annular tears involve extrusion of nucleus pulposus material through the annulus into the epidural space and produce irritation, through the dura, of the nerve roots by inflammatory modulators such as tumor necrosis factor-alpha. 131 The disc herniations and/or annular tears related to these symptoms often appear at L5eS1 and/or L4eL5 spinal levels.…”
Section: Region 3: Cauda Equinamentioning
confidence: 99%